Distributional decision-making of disadvantaged individuals: A proposal for an experimental extension - Patrick Oschwald; Eva Jacob; Adalbertus Kamanzi; Gudrun Kaufmann (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2024)
Societal structures play a crucial role when evaluating distributional outcomes. While social stratification may be more or less pronounced, most societies show some form of it. Being in a so-called "lower" social class often comes with economic uncertainty and is closely associated with a low household income (Western et al., 2012). The question is, if a redistribution scheme is chosen ex-ante via a social contract, or, redistributive measures are taken ex-post, how does the societal position play a role in this choice? As an outcome of the FRIBIS summer school 2023 on "Empirical methods of UBI investigations - Part II: The Social Contract: A Behavioral Economics Approach with Lab Experiments" we present here our extension for the experiment conducted by Faillo et al. (2015). The original experiment is based on contract theory in line with the tradition of Rawls A Theory of Justice (1971). Our extension, in a sense, lifts his proposed veil of ignorance and informs the disadvantaged of their societal position after a first round of the experiment. We begin with briefly describing the original experiment. Afterwards our proposed extension is described and contrasted against the outcomes of Faillo et al. (2015). We still have some reservations/doubts how far an approach with the "veil of ignorance" makes sense and what kind of (policy) implication could follow as logical outcome with respect to "terms of reality and power relations", which we will therefore discuss at the end.
Keywords: 330